The Influence Of Service Quality And Customer Satisfaction On Consumer Loyalty At Mondo Gelato Semarang - Maulidia Zakka Mustika; Mukhamad Kholil Aswan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study was conducted to analyze the effect of service quality and consumer satisfaction in Mondo Gelato Semarang and its impact on consumer loyalty in Mondo Gelato Semarang. This study uses convenience sampling with 105 respondents Mondo Gelato Semarang consumers who have made purchases more than 2 times. The analysis method used in this study is multiple linear regression analysis to determine the intervening variables. The findings of this study showed that the quality of Service and consumer satisfaction significantly affected consumer loyalty by 0.813. The variable quality of Service significantly affects consumer loyalty of 0.237, and the variable consumer satisfaction significantly of 0.576.